Pilot-scale pretreatments of sugarcane bagasse with steam explosion and mineral acid, organic acid, and mixed acids: synergies, enzymatic hydrolysis efficiencies, and structure-morphology correlations - Pal, Siddhartha; Joy, Shereena; Kumbhar, Pramod S.; Trimukhe, Kalpana D.; Gupta, Rishi; Kuhad, Ramesh Chander; Varma, Anjani J.; Shankar, Sasi (Biomass Conversion and Biorefinery, 2017)
In lignocellulosic (LC) ethanol processes, to facilitate enzymatic hydrolysis of cellulose, a physical chemical pretreatment is vital. In this study, we explored a single as well as a two-step physical-chemical pretreatment involving steam and mixed acid on unwashed sugarcane bagasse at pilot-scale level in a continuous horizontal reactor. To serve as a large-scale model, pretreatments were carried out at high solid levels of 18–20 % w/w. For the pretreatment, partial replacement of corrosive sulfuric acid with a milder acid-like oxalic acid was explored to derive possible advantages and synergies accruing by using a mixture of mineral acid and organic acid. The results of this work showed that first-step pretreatment carried out by the mixing of sulfuric acid (1.5 % w/w) and oxalic acid (1.5 % w/w) at 150 °C followed by a second-step steam explosion pretreatment at 180 °C gave significant synergies and advantages over other variants of pretreatments investigated, such as lower inhibitor levels and lower reaction severity. On post-pretreated bagasse, this study conducted comparative enzymatic hydrolysis study using a simple lab enzyme and a robust commercial enzyme. It was found that the addition of Tween 80 to the lab enzyme improved its performance to match the performance of the commercial enzyme. Scanning electron microscopy (SEM) studies were further carried out to correlate the morphology of pretreated samples with efficiency of enzyme hydrolysis. Besides morphological study, Fourier transform infrared (FTIR) studies of pretreated samples showed higher syringyl/guaiacyl ratio for all pretreatments, indicating lower levels of pseudo-lignins, which is beneficial for improved enzyme hydrolysis.